(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
This article considers some remarkably valuable glass finds from the roman site of Bedriacum (now Calvatone, CR), discovered during the 2005-2013 excavations in the “Quartiere degli artigiani” area (directed by professor Maria Teresa Grassi, Università degli Studi of Milan). These finds are dated between the end of the I century BC and the I century AD, a period in which the vicus was particularly prosperous. The focus will be on mosaic glass finds, cast monochrome glass (a cup type Is.20, the first evidence of this type of glass from Bedriacum, a linear cut bowl type Is.1/18 and two ribbed bowls type Is.3), mold-blown glass (two fragments of cups inspired by the Ennion production, a truncated conical beaker type Is.31) and free blown glass vessels (two ribbed bowls type Is.17 and some fragments with blobbed decoration).